Vocation and social context - Giordan, Giuseppe. (Religion and the social order, 2007)
The category of Beruf has intrigued sociology since Max Weber made it a fundamental element in understanding the relationship between the individual and society. The richness of the concept can be found in the simultaneous polarity and interpenetration between the subject's personal profession and the feeling of a call from God: precisely this ambiguity widens the possibility of applying the concept in understanding the meaning that individuals give to their own professions, activities and, more generally, \'life in the world." Illustrating the different ways in which "vocation-profession" can be interpreted, and how it can be studied from various perspectives and with different scientific sensibilities, this book demonstrates how the concept of Beruf continues to be fertile for contemporary sociology. Contributors: Anthony J. Blasi, Andrew J. Weigert, Franco Garelli, Luigi Berzano, Robert M. Fishman, Keeley S. Jones, Laura M. Leming, Giovanni Dal Piaz, Robert C. Butler